GAMBARAN ASAM URAT PADA LANSIA DI PUSKESMAS CELIKAH KAYUAGUNG - Liliana, Ranti; Fitri Aprianti; Heryanti (Jurnal Kesehatan dan Pembangunan, 2025)
The abnormal levels of uric acid in the blood generally occur in men of advanced age, while in women it is found during menopause. This study aims to determine the profile of blood uric acid levels in elderly patients at the Celikah Kayuagung public health center in 2025. This research uses a descriptive method, with 20 samples examined using accidental sampling, conducted at the Elderly Integrated Health Service and carried out at the Celikah Kayuagung public health center in 2025. The analysis results showed that 10 elderly individuals (50%) had hyperuricemia and 10 individuals (50%) were normal. Based on the age of the elderly, in the early elderly group (46-55 years), no cases of hyperuricemia were found, and 1 individual (100%) was normal in the late elderly age group (56-65 years). In the upper elderly age group (65 years and above), there were 5 individuals (50%) with hyperuricemia and 5 individuals (50%) normal, and in the 55.6% with hyperuricemia and 4 individuals (44.4%) normal Based on gender, it was found that 4 people (57.1%) had hyperuricemia and 3 people (42.9%) were normal among males, whereas among females, 6 people (46.2%) had hyperuricemia and 7 people (53.8%) were normal. It is advised for the elderly to continue to apply a healthy lifestyle by exercising regularly, reducing high purine consumption, avoiding alcohol, and not smoking.